The Relationship between Spiritual Health and Resilience in Hemodialysis Patients - A Ebrahimi (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: Chronic kidney disease is one of the major health problems in today's world that creates a threatening situation for the health and socioeconomic status of the affected person, his/her family and the whole society. Due to the fact that in chronic diseases, a spiritual crisis appears in the individual, this study was therefore conducted to investigate the effect of spiritual health on resilience in patients undergoing hemodialysis. METHODS: This cross-sectional study was performed on 130 patients undergoing hemodialysis in Shahid Beheshti Hospital in Babol in 2017-2018. Data were collected and analyzed using Spiritual Well Being Scale (SWBS) (Paloutzian & Ellison) with a score of 20-125 at three levels of low, medium and high, as well as Connor-Davidson Resilience scale (CD-RISC) with a score of 20-125 at three levels of low, medium and high. FINDINGS: In this study, 5 (3.8%) patients had low, 81 (62.3%) had medium and 44 (33.8%) had high spiritual health. The mean score of spiritual health was 87.80±21.12 and was at a medium level. Furthermore, 6 patients (4.6%) had low resilience, 95 patients (73.1%) had medium and 29 patients (22.3%) had high resilience. The mean total resilience score was 86.63±19.48 and was at a medium level. The relationship between spiritual health and resilience was direct and significant (p<0.001, r=0.62). CONCLUSION: The present study showed that spiritual health has a significant and positive relationship with resilience of patients undergoing hemodialysis treatment.